2020
DOI: 10.1371/journal.pone.0238979
|View full text |Cite|
|
Sign up to set email alerts
|

Go big or go home: A model-based assessment of general strategies to slow the spread of forest pests via infested firewood

Abstract: Invasive pests, such as emerald ash borer or Asian longhorn beetle, have been responsible for unprecedented ecological and economic damage in eastern North America. These and other wood-boring invasive insects can spread to new areas through human transport of untreated firewood. Behaviour, such as transport of firewood, is affected not only by immediate material benefits and costs, but also by social forces. Potential approaches to reduce the spread of wood-boring pests through firewood include raising awaren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Despite the uncertainties surrounding biological control, relying on the past quarantine measures and adherence levels did not limit EAB expansion to the extent desired by state and federal agencies. Jentsch et al (2020) found that only extremely high management effectiveness would reduce EAB spread rates with recreational travelers, whether this took the form of a high compliance, large quarantine zone, or high rates of firewood interception at highway checkpoints. The authors pointed to low levels of public outreach and low quarantine budgets as the source of current underperforming control measures.…”
Section: Milp Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the uncertainties surrounding biological control, relying on the past quarantine measures and adherence levels did not limit EAB expansion to the extent desired by state and federal agencies. Jentsch et al (2020) found that only extremely high management effectiveness would reduce EAB spread rates with recreational travelers, whether this took the form of a high compliance, large quarantine zone, or high rates of firewood interception at highway checkpoints. The authors pointed to low levels of public outreach and low quarantine budgets as the source of current underperforming control measures.…”
Section: Milp Formulationmentioning
confidence: 99%
“…Conventional strategies based on these models tend to target the pest invasion front (or leading edge, (Sharov et al, 2002)), without considering the ability of major cities to act as hubs of long-distance pest transport via the road network (Chivers & Leung, 2012;Hudgins et al, 2017;Yemshabov et al, 2015). While these strategies have been demonstrably effective for species whose landscape-scale spread is dominated by natural dispersal (Sharov et al, 2002), EAB spread is known to be driven by anthropogenic transport (Jentsch et al, 2020;Ward et al, 2020), and several models exist that account for human population density as an attractor of EAB propagules (Ward et al, 2020;. Indeed, from 2012 to 2021, the domestic quarantine effort undertaken by the US Department of Agriculture's Animal and Plant Health Inspection Service (APHIS) to control EAB only regulated outbound movement from a fairly contiguous suite of infested areas (McCullough, 2020;APHIS, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…Social media data has also been used to reconstruct user networks based on interactions and examine homophily within these networks [ 148 ], which can inform CHES network models. Empirical trade and transport networks can provide important insights into the spatial CHES coupling as well as human metapopulation models [ 151 ], having already been applied to CHES models for invasive species [ 152 , 153 ] and land use via global food trade [ 92 , 154 ].…”
Section: Gaps and Promising Future Directions In Ches Modellingmentioning
confidence: 99%
“…Despite the uncertainties surrounding biological control, relying on the past quarantine measures and adherence levels has been insufficient to limit EAB expansion. Jentsch et al [50] found that only extremely high management effectiveness would reduce EAB spread rates with recreational travelers, whether this took the form of a high compliance, large quarantine zone, or high rates of firewood interception at highway checkpoints. The authors pointed to low levels of public outreach and low quarantine budgets as the source of current ineffective control measures.…”
Section: Present-day Eab Management Techniquesmentioning
confidence: 99%